Solid-state battery positive electrode and preparation method and application thereof

By blending the positive electrode material with the solid electrolyte material in the positive electrode of the solid battery and controlling the increase in the molar content gradient to form a multi-level diffusion mass transfer structure, the problem of poor interface performance between the positive electrode material and the electrolyte is solved, and more efficient lithium ion transmission and battery performance improvement is achieved.

CN119725538APending Publication Date: 2025-03-28JINGMEN GEM NEW MATERIAL CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411900961.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the prior art, the interface performance between the positive electrode material of the solid-state battery and the solid-state electrolyte is poor, resulting in problems such as interfacial side reactions and large interface impedance and structural degradation.

Method used

By blending the positive electrode material with the solid electrolyte material and controlling the molar content of the solid electrolyte material to increase the gradient in the thickness direction of the positive electrode, a multi-level diffusion mass transfer structure is formed to optimize the transmission path of lithium ions.

Benefits of technology

The performance of the interface between the positive electrode material and the electrolyte is improved, the interface side reactions and impedance are reduced, the removal and embedding efficiency of lithium ions is improved, and the electrochemical performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725538A_ABST
    Figure CN119725538A_ABST
Patent Text Reader

Abstract

The invention discloses a solid-state battery positive electrode and a preparation method and application thereof. The solid-state battery positive electrode comprises at least two positive electrode material layers, each positive electrode material layer comprises a positive electrode material and a solid-state electrolyte material, and the molar content of the solid-state electrolyte material in the positive electrode material layer is gradually increased in the direction from one side of the positive electrode to the other side of the positive electrode. Transition between traditional two-phase materials is improved, separation of positive electrode lithium ions is accelerated through multi-level diffusion mass transfer, and a transmission path of the lithium ions between a positive electrode and a solid electrolyte interface is optimized, so that the purpose of improving the positive electrode material and the electrolyte interface is achieved. The problems of large interface side reaction, large interface impedance and structure degradation of the positive electrode material in the prior art are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to a solid-state battery and relates to a solid-state battery positive electrode and a preparation method and application thereof. Background Art

[0002] All-solid-state battery (SSB) is considered an important development of next-generation battery technology, mainly used to improve battery safety, energy density and life. At present, the core issue restricting the further development of all-solid-state batteries is how to achieve a good solid-solid contact interface between the positive electrode material and the solid electrolyte.

[0003] Many scientific researchers have carried out comprehensive and detailed work around this issue. For example, a patent has been published that discloses a secondary coating method in which the positive electrode material is first coated with a layer of zirconium alkoxide, and then coated with a mixture of lithium alkoxide, lanthanum alkoxide, and zirconium alkoxide. The prepared positive electrode material is used in all-solid-state batteries, and the interface compatibility between the active material and the solid electrolyte is good, the cycle performance is stable, and the safety is good. In addition, there is a patent published that discloses a multi-element sulfur-containing positive electrode material. This material uses the doping of anion S to effectively inhibit the serious space charge layer effect and element interdiffusion between the sulfide electrolyte and the layered oxide positive electrode material, reduce the interfacial electrochemical side reactions, thereby increasing the capacity, reducing the interfacial impedance, and optimizing the electrochemical performance of the material.

[0004] Coating modification of positive electrode materials is an effective way to achieve good contact between positive electrode materials and electrolytes. However, this process often faces problems such as complicated preparation process, difficult control of key parameters (such as coating amount and coating thickness), and increased costs. In addition, the coating modification method has changed from a simple two-phase interface to a multi-phase complex interface (interface between positive electrode material and coating layer; interface between coating layer and electrolyte). Although it can weaken the mass transfer barrier between positive electrode materials and electrolyte materials and effectively enhance the ion transfer between the positive electrode and electrolyte interfaces, it significantly increases the complexity of the study of interfacial mass transfer mechanisms.

[0005] Doping modification of positive electrode materials is also a common and effective means to improve the contact between positive electrode materials and electrolytes. The doping elements must not only show structural and phase stability at high temperatures to the main material, but also ensure good physical / chemical stability in direct contact with the electrolyte material. However, doping modification also faces increased costs, and more importantly, the uniformity of doping often faces huge challenges. Uneven doping will lead to reduced modification effects.

[0006] Therefore, providing a method and positive electrode that can improve the interface performance between the positive electrode material and the solid electrolyte of a solid-state battery is a technical problem that needs to be solved urgently. Summary of the invention

[0007] In view of the above-mentioned technical problems existing in the prior art, the object of the present invention is to provide a solid-state battery positive electrode and a preparation method and application thereof.

[0008] To achieve the above object, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a solid-state battery positive electrode, which includes at least two layers of positive electrode material layers, each of which includes a positive electrode material and a solid electrolyte material, and the molar content of the solid electrolyte material in the positive electrode material layer increases along the direction from one side to the other side of the positive electrode.

[0010] The present invention improves the transition between the traditional two-phase materials by blending the positive electrode material and the solid electrolyte material and controlling the molar content of the solid electrolyte material to increase gradually in the thickness direction of the positive electrode. The multi-level diffusion mass transfer accelerates the release of positive electrode lithium ions and optimizes the transmission path of lithium ions between the positive electrode and the solid electrolyte interface, thereby achieving the purpose of improving the interface between the positive electrode material and the electrolyte. The problems of interface side reactions, large interface impedance and structural degradation faced by the positive electrode material in the prior art are solved.

[0011] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0012] Preferably, the number of the positive electrode material layers is 4 to 6, for example, 4, 5 or 6 layers.

[0013] Preferably, between adjacent positive electrode material layers, the difference in the molar content of the solid electrolyte material is 10% to 40% based on the molar amount of the positive electrode material, for example, it can be 10%, 12%, 15%, 17%, 20%, 23%, 26%, 28%, 30%, 32%, 35%, 36%, 38% or 40%, etc.

[0014] Preferably, in the positive electrode material layer, based on the molar amount of the positive electrode material, the molar content of the solid electrolyte material is 5% to 95%, for example, it can be 5%, 10%, 15%, 20%, 23%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90% or 95%, etc.

[0015] Preferably, the solid-state battery positive electrode includes 5 layers of positive electrode material layers, each of the positive electrode material layers includes positive electrode material and solid electrolyte material, and along the direction from one side of the positive electrode to the other side, the molar content of the solid electrolyte material in the positive electrode material layer is 5% to 15%, 25% to 35%, 45% to 55%, 65% to 75%, and 85% to 95%, respectively.

[0016] In one embodiment, the contents in the two outermost positive electrode material layers of the positive electrode are 5% to 15% and 85% to 95% respectively.

[0017] Preferably, the total thickness of the positive electrode material layer is 10μm to 500μm, for example, it can be 10μm, 20μm, 30μm, 40μm, 60μm, 80μm, 100μm, 120μm, 140μm, 160μm, 180μm, 200μm, 220μm, 240μm, 260μm, 280μm, 300μm, 320μm, 340μm, 350μm, 370μm, 380μm, 400μm, 425μm, 450μm, 470μm, 480μm or 500μm, etc.

[0018] Preferably, the solid electrolyte material in each of the positive electrode material layers independently includes at least one of an oxide solid electrolyte and a sulfide solid electrolyte.

[0019] Preferably, the oxide solid electrolyte comprises lithium zirconium phosphate oxide (LiZr 2 (PO 4 ) 3 , LZP), lithium titanium phosphate oxide (LiTi 2 (PO 4 ) 3 , LTP), lithium germanium phosphate (LiGe 2 (PO 4 ) 3 , LGP), lithium lanthanum titanium oxide (Li 3x La 2 / 3-x TiO 3 , x = 0.01 ~ 0.15, LLTO), lithium lanthanum zirconium oxide (Li 7 La 3 Zr 2 O 12 , LLZO) and niobium-doped lithium lanthanum zirconium oxide (Li 6.5 La 3 Zr 1.5 Ta 0.5-x Nb x O 12 , x=0.01~0.15, at least one of NT-LLZO).

[0020] Preferably, the sulfide solid electrolyte comprises lithium thiophosphate (Li 3 PS 4 , LPS), argyrodite electrolyte (Li 6 PS 5 Cl, LPSCl), lithium germanium phosphosulfide (Li 10 G 2 S 12 , LGPS), zinc-doped sulfide solid electrolyte (Li 3+ 3x P 1-x Zn x S 4-x O x , 0.01≤x≤0.15, LPZSO) and manganese-doped sulfide solid electrolytes (Li 7 P 3-x Mn x S 11-3x I 3x , 0.01≤x≤0.15, LPMSI).

[0021] In a second aspect, the present invention provides a method for preparing a solid-state battery positive electrode as described in the first aspect, the preparation method comprising the following steps:

[0022] (1) mixing the cathode material and the solid electrolyte material by ball milling according to different mass ratios to obtain at least two series of composite cathode materials;

[0023] (2) assembling the above-mentioned at least two series of composite positive electrode materials according to the increasing molar content of the solid electrolyte material, and compacting them to obtain the solid-state battery positive electrode; or,

[0024] According to the increasing molar content of the solid electrolyte material, the above-mentioned at least two series of composite positive electrode materials are respectively prepared into slurries with a binder and a solvent and coated on the surface of the current collector. After drying, a solid-state battery positive electrode is obtained.

[0025] The method of the present invention prepares a series of composite positive electrode materials with different gradients of solid electrolyte materials by means of blending and ball milling, and compacts them after assembly to obtain a solid-state battery positive electrode. The method is simple to operate and has good universality. Moreover, it has excellent results in improving the interface between the positive electrode material and the solid electrolyte.

[0026] Preferably, the ball milling mixing includes coarse ball milling and fine ball milling performed sequentially.

[0027] In the prior art, materials are melted under high temperature and high pressure to form crystals, which are often in the form of blocks or sheets after sintering. When such materials are ground into powders by ordinary grinding, they cannot be used as battery materials for ion-scale transmission.

[0028] The present invention synthesizes high-performance solid electrolyte materials through rough ball milling and fine ball milling. The rough ball milling is carried out under low ball milling energy, mainly to crush the block or sheet material to make it into a powder material. At this time, the particles are relatively large, generally above 100 μm. The subsequent fine ball milling significantly increases the ball milling energy. On the one hand, the powder material is refined and the particle size is further reduced, generally less than 10 μm or even nanometer level. On the other hand, high ball milling energy provides a guarantee for uniformity and mixing consistency. In addition, ball milling in two times can protect the equipment and reduce safety risks. When large block and sheet materials are directly operated at high speed and high load, the equipment will be damaged and accompanied by certain safety risks.

[0029] Preferably, the process parameters of the rough ball milling are: rotation speed 400rpm~800rpm, for example, it can be 400rpm, 450rpm, 500rpm, 550rpm, 600rpm, 650rpm, 700rpm, 750rpm or 800rpm; time 3h~8h, for example, it can be 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h or 8h.

[0030] Preferably, when the mass proportion of the sulfide solid electrolyte in the solid electrolyte material is ≥50% (for example, it can be 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or 100%, etc.), the process parameters of the rough ball milling are: rotation speed 400rpm~600rpm (for example, it can be 400rpm, 450rpm, 500rpm, 550rpm or 600rpm, etc.), time 3h~5h (for example, it can be 3h, 3.5h, 4h, 4.5h or 5h, etc.). In this preferred technical solution, the solid electrolyte material can be all sulfide solid electrolytes, or it can be a mixture of sulfide solid electrolytes and oxide solid electrolytes.

[0031] Preferably, when the mass proportion of the oxide solid electrolyte in the solid electrolyte material is ≥50% (for example, it can be 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or 100%, etc.), the process parameters of the rough ball milling are: rotation speed 600rpm~800rpm (for example, it can be 600rpm, 650rpm, 700rpm, 750rpm or 800rpm, etc.), time 5h~8h (for example, it can be 5h, 5.5h, 6h, 6.5h, 7h, 7.5h or 8h, etc.). In this preferred technical solution, the solid electrolyte material can be all oxide solid electrolytes, or it can be a mixture of sulfide solid electrolytes and oxide solid electrolytes.

[0032] Preferably, the process parameters of the refining ball milling are: rotation speed 800rpm~1200rpm, for example, it can be 800rpm, 850rpm, 900rpm, 950rpm, 1000rpm, 1050rpm, 1100rpm, 1150rpm or 1200rpm, etc.; time 6h~12h, for example, it can be 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 10h, 10.5h, 11h, 11.5h or 12h, etc.

[0033] Preferably, when the mass proportion of the sulfide solid electrolyte in the solid electrolyte material is ≥50% (for example, it can be 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or 100%, etc.), the process parameters of the refined ball milling are: rotation speed 800rpm~1000rpm (for example, it can be 800rpm, 850rpm, 900rpm, 950rpm or 1000rpm, etc.), time 6h~8h (for example, it can be 6h, 6.5h, 7h, 7.5h or 8h, etc.). In this preferred technical solution, the solid electrolyte material can be all sulfide solid electrolytes, or it can be a mixture of sulfide solid electrolytes and oxide solid electrolytes.

[0034] Preferably, when the mass proportion of the oxide solid electrolyte in the solid electrolyte material is ≥50% (for example, it can be 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or 100%, etc.), the process parameters of the refined ball milling are: rotation speed 1000rpm~1200rpm (for example, it can be 1000rpm, 1050rpm, 1100rpm, 1150rpm or 1200rpm, etc.), time 8h~12h (for example, it can be 8h, 8.5h, 9h, 9.5h, 10h, 10.5h, 11h or 12h, etc.). In this preferred technical solution, the solid electrolyte material can be all oxide solid electrolytes, or it can be a mixture of sulfide solid electrolytes and oxide solid electrolytes.

[0035] As a preferred technical solution of the preparation method of the present invention, the compaction is carried out under a pressure of 100 MPa to 300 MPa. The pressure can be, for example, 100 MPa, 110 MPa, 120 MPa, 130 MPa, 140 MPa, 150 MPa, 160 MPa, 170 MPa, 180 MPa, 190 MPa, 200 MPa, 210 MPa, 220 MPa, 230 MPa, 240 MPa, 250 MPa, 260 MPa, 270 MPa, 280 MPa, 290 MPa or 300 MPa.

[0036] Preferably, when the mass proportion of the sulfide solid electrolyte in the solid electrolyte material is ≥50% (for example, it can be 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or 100%, etc.), the compaction is carried out under a pressure of 100MPa to 150MPa (for example, it can be 100MPa, 110MPa, 120MPa, 130MPa, 140MPa or 150MPa, etc.). In this preferred technical solution, the solid electrolyte material can be all sulfide solid electrolytes, or it can be a mixture of sulfide solid electrolytes and oxide solid electrolytes.

[0037] Preferably, when the mass proportion of the oxide solid electrolyte in the solid electrolyte material is ≥50% (for example, it can be 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or 100%, etc.), the compaction is carried out under a pressure of 150MPa to 300MPa (for example, it can be 150MPa, 160MPa, 170MPa, 180MPa, 190MPa, 200MPa, 210MPa, 220MPa, 230MPa, 240MPa, 250MPa, 260MPa, 270MPa, 280MPa, 290MPa or 300MPa, etc.). In this preferred technical solution, the solid electrolyte material can be all oxide solid electrolytes, or it can be a mixture of sulfide solid electrolytes and oxide solid electrolytes.

[0038] There are significant differences in hardness between oxide solid electrolytes and sulfide solid electrolytes. Sulfide solid electrolytes are usually soft and easy to contact with positive and negative electrode materials, while oxide solid electrolytes are relatively hard. The present invention fully considers the differences in properties between oxide solid electrolytes and sulfide solid electrolytes, adjusts the parameters of ball milling and pressing, and can better ensure that the material has a suitable particle size, good dispersibility and mixing effect, and ensures good contact between materials.

[0039] In a third aspect, the present invention provides a solid-state battery, comprising a positive electrode, a negative electrode, and a solid electrolyte layer located between the positive electrode and the negative electrode, characterized in that the positive electrode adopts the solid-state battery positive electrode described in the first aspect, and the side with a low content of solid electrolyte material in the solid-state battery positive electrode faces the solid electrolyte layer.

[0040] The present invention does not specifically limit the method for preparing the solid-state battery, and those skilled in the art can prepare it according to the method disclosed in the prior art.

[0041] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0042] Compared with the prior art, the present invention has the following beneficial effects:

[0043] (1) The present invention improves the transition between the traditional two-phase materials by blending the positive electrode material and the solid electrolyte material and controlling the gradient increase of the solid electrolyte material in the thickness direction of the positive electrode. The multi-level diffusion mass transfer accelerates the release of positive electrode lithium ions and optimizes the transmission path of lithium ions between the positive electrode and the solid electrolyte interface, thereby achieving the purpose of improving the interface between the positive electrode material and the electrolyte. The problems of interface side reactions, large interface impedance and structural degradation faced by the positive electrode materials in the prior art are solved.

[0044] (2) The method of the present invention is simple to operate and has good universality. It also has excellent effect on improving the interface between the positive electrode material and the solid electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 It is a process flow chart of a solid-state battery positive electrode provided by one embodiment of the present invention. DETAILED DESCRIPTION

[0046] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.

[0047] The specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0048] Preparation Example 1

[0049] This preparation example provides a sulfide solid electrolyte, the chemical formula of which is Li 3.5 P 0.5 Zn 0.5 S 3.5 O 0.5 , referred to as LPZSO. The preparation method comprises the following steps:

[0050] The raw materials lithium sulfide, phosphorus pentasulfide and zinc oxide were ball-milled and mixed and then sintered. The ball-milling time was 13.5 hours, the sintering temperature was 250°C, and the sintering insulation time was 4 hours. LPZSO-type solid electrolyte material with excellent performance was synthesized.

[0051] Preparation Example 2

[0052] This preparation example provides a sulfide solid electrolyte, the chemical formula of which is Li 7 P 2.9 Mn 0.1 S 10.7 I 0.3 , referred to as LPMSI. The preparation method comprises the following steps:

[0053] The raw materials lithium sulfide, phosphorus pentasulfide, manganese sulfide and lithium iodide were ball-milled and mixed and then sintered. The ball-milling time was 30 hours, the sintering temperature was 250°C, and the sintering insulation time was 2 hours to synthesize an LPMSI type solid electrolyte material with excellent performance.

[0054] Preparation Example 3

[0055] This preparation example provides an oxide solid electrolyte, the chemical formula of which is Li 6.5 La 3 Zr 1.5 Ta 0.3 Nb 0.2 O 12 , referred to as NT-LLZO. The preparation method comprises the following steps:

[0056] The raw materials lanthanum oxide, tantalum oxide, niobium oxide, zirconium oxide and an excess of 15% (molar amount) lithium hydroxide were wet-ground with ethanol as the medium for 6 hours. After drying to remove the solvent, they were sintered at 1150°C for 6 hours to obtain an NT-LLZO solid electrolyte material with excellent performance.

[0057] Example 1

[0058] This embodiment provides a solid-state battery positive electrode, the solid-state battery positive electrode includes three layers of positive electrode material layers, each of which includes a positive electrode material (lithium cobalt oxide, LiCoO 2 , referred to as LCO) and a solid electrolyte material (Preparation Example 1), wherein the molar contents of the solid electrolyte material in the positive electrode material layer are 10%, 50% and 90% respectively along the direction from one side to the other side of the positive electrode;

[0059] In this embodiment, the total thickness of the three positive electrode material layers is 300 μm.

[0060] This embodiment also provides a method for preparing the above-mentioned solid-state battery positive electrode, comprising the following steps:

[0061] S1: Preparation of composite cathode materials I

[0062] The positive electrode material and the solid electrolyte material were added to a planetary ball mill at a molar ratio of 100:10, and the first rough ball milling was performed at a rotation speed of 500 rpm for 4 hours, and then the second fine ball milling was performed at a rotation speed of 800 rpm for 8 hours to obtain a composite positive electrode material I.

[0063] S2: Preparation of composite cathode materials II

[0064] The positive electrode material and the solid electrolyte material were added to a planetary ball mill at a molar ratio of 100:50, and the first rough ball milling was performed at a rotation speed of 500 rpm for 4 hours, and then the second fine ball milling was performed at a rotation speed of 900 rpm for 7 hours to obtain a composite positive electrode material II.

[0065] S3: Preparation of composite cathode materials III

[0066] The positive electrode material and the solid electrolyte material were added to a planetary ball mill at a molar ratio of 100:90, and the first rough ball milling was performed at a rotation speed of 500 rpm for 4 hours, and then the second fine ball milling was performed at a rotation speed of 800 rpm for 8 hours to obtain a composite positive electrode material III.

[0067] S4: Take the above-mentioned composite positive electrode material I, composite positive electrode material II and composite positive electrode material III, and perform graded gradient assembly in the order of increasing molar content of solid electrolyte, and compact them at 125 MPa to obtain a gradient positive electrode product, that is, a solid-state battery positive electrode.

[0068] Application Example 1

[0069] This application example provides an all-solid-state battery (LCO@LPZSO│LPZSO│Li all-solid-state battery), including a positive electrode, a negative electrode, and a solid electrolyte layer located between the positive electrode and the negative electrode, wherein the positive electrode is the solid-state battery positive electrode of Example 1, the negative electrode is lithium foil, and the solid electrolyte layer is a LPZSO solid electrolyte layer.

[0070] Example 2

[0071] This embodiment provides a solid-state battery positive electrode, the solid-state battery positive electrode comprising three positive electrode material layers, each of the positive electrode material layers comprising a positive electrode material (elemental sulfur, S) and a solid electrolyte material (Preparation Example 1), and along the direction from one side to the other side of the positive electrode, the molar content of the solid electrolyte material in the positive electrode material layer is 30%, 60% and 80% respectively;

[0072] In this embodiment, the total thickness of the three positive electrode material layers is 200 μm.

[0073] This embodiment also provides a method for preparing the above-mentioned solid-state battery positive electrode, comprising the following steps:

[0074] S1: Preparation of composite cathode materials I

[0075] The positive electrode material and the solid electrolyte material were added to a planetary ball mill at a molar ratio of 100:30, and the first rough ball milling was performed at a rotation speed of 400 rpm for 5 h, and then the second fine ball milling was performed at a rotation speed of 800 rpm for 8 h to obtain a composite positive electrode material I.

[0076] S2: Preparation of composite cathode materials II

[0077] The positive electrode material and the solid electrolyte material were added to a planetary ball mill at a molar ratio of 100:60, and the first rough ball milling was performed at a rotation speed of 400 rpm for 5 h, and then the second fine ball milling was performed at a rotation speed of 900 rpm for 7 h to obtain a composite positive electrode material II.

[0078] S3: Preparation of composite cathode materials III

[0079] The positive electrode material and the solid electrolyte material were added to a planetary ball mill at a molar ratio of 100:80, and the first rough ball milling was performed at a rotation speed of 400 rpm for 5 h, and then the second fine ball milling was performed at a rotation speed of 800 rpm for 8 h to obtain a composite positive electrode material III.

[0080] S4: Take the above-mentioned composite positive electrode material I, composite positive electrode material II and composite positive electrode material III, and perform graded gradient assembly in the order of increasing molar content of solid electrolyte, and compact them at 140 MPa to obtain a gradient positive electrode product, that is, a solid-state battery positive electrode.

[0081] Application Example 2

[0082] This application example provides an all-solid-state battery (S@LPMSI│LPMSI│Li-In all-solid-state battery), including a positive electrode, a negative electrode, and a solid electrolyte layer located between the positive electrode and the negative electrode, wherein the positive electrode is the positive electrode of the solid-state battery of Example 2, the negative electrode is a lithium-indium alloy, and the solid electrolyte layer is an LPMSI solid electrolyte layer, wherein the lithium-indium alloy is in contact with the solid electrolyte layer in advance, and the method is: using an In sheet with a specification of Φ10mm (thickness of 100μm) and a Li sheet with a specification of Φ8mm (thickness of 100μm). The In sheet is attached to the electrolyte, and the lithium sheet is attached to the surface of the In sheet, and the lithium-indium alloy is fully in contact with the electrolyte under an equivalent pressure of 6MPa. After standing for 6h, Li-In diffuses into each other to form a Li-In alloy.

[0083] Example 3

[0084] This embodiment provides a solid-state battery positive electrode, the solid-state battery positive electrode comprising 4 positive electrode material layers, each of the positive electrode material layers comprising a positive electrode material (lithium iron phosphate, LFP) and a solid electrolyte material (Preparation Example 3), and along the direction from one side to the other side of the positive electrode, the molar content of the solid electrolyte material in the positive electrode material layer is 10%, 30%, 70% and 90% respectively;

[0085] In this embodiment, the total thickness of the four positive electrode material layers is 400 μm.

[0086] This embodiment also provides a method for preparing the above-mentioned solid-state battery positive electrode, comprising the following steps:

[0087] S1: Preparation of composite cathode materials I

[0088] The positive electrode material and the solid electrolyte material were added to a planetary ball mill at a molar ratio of 100:10, and the first rough ball milling was performed at a rotation speed of 700 rpm for 6 h, and then the second fine ball milling was performed at a rotation speed of 1200 rpm for 10 h to obtain a composite positive electrode material I.

[0089] S2: Preparation of composite cathode materials II

[0090] The positive electrode material and the solid electrolyte material were added to a planetary ball mill at a molar ratio of 100:30, and the first rough ball milling was performed at a rotation speed of 700 rpm for 6 hours, and then the second fine ball milling was performed at a rotation speed of 1200 rpm for 10 hours to obtain a composite positive electrode material II.

[0091] S3: Preparation of composite cathode materials III

[0092] The positive electrode material and the solid electrolyte material were added to a planetary ball mill at a molar ratio of 100:70, and the first rough ball milling was performed at a rotation speed of 700 rpm for 6 hours, and then the second fine ball milling was performed at a rotation speed of 1200 rpm for 10 hours to obtain a composite positive electrode material III.

[0093] S4: Preparation of composite cathode materials IV

[0094] The positive electrode material and the solid electrolyte material were added to a planetary ball mill at a molar ratio of 100:90, and the first rough ball milling was performed at a rotation speed of 700 rpm for 6 hours, and then the second fine ball milling was performed at a rotation speed of 1200 rpm for 10 hours to obtain a composite positive electrode material IV.

[0095] S5: Take the above-mentioned composite positive electrode material I, composite positive electrode material II, composite positive electrode material III and composite positive electrode material IV, mix them with binder PVDF and NMP to prepare slurry I, slurry II, slurry III and slurry IV. In these four slurries, the content of PVDF accounts for 3% of the total solid mass of the corresponding slurry. They are coated on the surface of aluminum foil in the order of increasing molar content of solid electrolyte and dried to obtain a gradient positive electrode product, that is, a solid-state battery positive electrode.

[0096] Application Example 3

[0097] This application example provides an all-solid-state battery (LFP@NT-LLZO│NT-LLZO│Li-InF 3A solid-state battery) includes a positive electrode, a negative electrode, and a solid electrolyte layer located between the positive electrode and the negative electrode, wherein the positive electrode is the positive electrode of the solid-state battery in Example 3, the negative electrode is a lithium indium fluoride alloy, and the solid electrolyte layer is a NT-LLZO solid electrolyte layer. The lithium indium fluoride alloy is in contact with the solid electrolyte layer in advance, and the method is: melt an appropriate amount of metallic lithium in a crucible, add 5wt% InF 3 The powder is stirred evenly, and one side of the NT-LLZO electrolyte sheet is placed in the crucible so that the molten liquid adheres to one side of the NT-LLZO electrolyte sheet. After sufficient cooling, the contact between the electrolyte and the negative electrode is completed.

[0098] Example 4

[0099] This embodiment provides a solid-state battery positive electrode, the solid-state battery positive electrode includes 5 layers of positive electrode material layers, each of which includes a positive electrode material (lithium cobalt oxide, LiCoO 2 ) and solid electrolyte material (lithium germanium phosphosulfide, chemical formula Li 10 G 2 S 12 , referred to as LGPS), along the direction from one side to the other side of the positive electrode, the molar content of the solid electrolyte material in the positive electrode material layer is 10%, 30%, 50%, 70% and 90% respectively;

[0100] In this embodiment, the total thickness of the five positive electrode material layers is 500 μm.

[0101] This embodiment also provides a method for preparing the above-mentioned solid-state battery positive electrode. The process flow chart is shown in Figure 1 , including the following steps:

[0102] S1: Preparation of composite cathode materials I

[0103] The positive electrode material and the solid electrolyte material were added to a planetary ball mill at a molar ratio of 100:10, and the first rough ball milling was performed at a rotation speed of 500 rpm for 4 hours, and then the second fine ball milling was performed at a rotation speed of 900 rpm for 7 hours to obtain a composite positive electrode material I.

[0104] S2: Preparation of composite cathode materials II

[0105] The positive electrode material and the solid electrolyte material were added to a planetary ball mill at a molar ratio of 100:30, and the first rough ball milling was performed at a rotation speed of 500 rpm for 4 hours, and then the second fine ball milling was performed at a rotation speed of 900 rpm for 7 hours to obtain a composite positive electrode material II.

[0106] S3: Preparation of composite cathode materials III

[0107] The positive electrode material and the solid electrolyte material were added to a planetary ball mill at a molar ratio of 100:50, and the first rough ball milling was performed at a rotation speed of 500 rpm for 4 hours, and then the second fine ball milling was performed at a rotation speed of 900 rpm for 7 hours to obtain a composite positive electrode material III.

[0108] S4: Preparation of composite cathode materials IV

[0109] The positive electrode material and the solid electrolyte material were added to a planetary ball mill at a molar ratio of 100:70, and the first rough ball milling was performed at a rotation speed of 500 rpm for 4 hours, and then the second fine ball milling was performed at a rotation speed of 900 rpm for 7 hours to obtain a composite positive electrode material IV.

[0110] S5: Preparation of composite cathode material V

[0111] The positive electrode material and the solid electrolyte material were added to a planetary ball mill at a molar ratio of 100:90, and the first rough ball milling was performed at a rotation speed of 500 rpm for 4 hours, and then the second fine ball milling was performed at a rotation speed of 900 rpm for 7 hours to obtain a composite positive electrode material V.

[0112] S6: Take the above-mentioned composite positive electrode material I, composite positive electrode material II, composite positive electrode material III, composite positive electrode material IV, and composite positive electrode material V, and perform graded gradient assembly in the order of increasing molar content of solid electrolyte, and compact them at 125 MPa to obtain a gradient positive electrode product, that is, a solid-state battery positive electrode.

[0113] Application Example 4

[0114] This application example provides an all-solid-state battery, which differs from application example 1 in that the solid-state battery positive electrode of embodiment 1 is replaced by the solid-state battery positive electrode of embodiment 4.

[0115] Example 5

[0116] This embodiment provides a solid-state battery positive electrode, the solid-state battery positive electrode includes 4 layers of positive electrode material layers, each of which includes a positive electrode material (lithium cobalt oxide, LiCoO 2 ) and solid electrolyte material (lithium titanium phosphate oxide, chemical formula LiTi 2 (PO 4 ) 3 , referred to as LTP), along the direction from one side to the other side of the positive electrode, the molar content of the solid electrolyte material in the positive electrode material layer is 10%, 30%, 70% and 90% respectively;

[0117] In this embodiment, the total thickness of the four positive electrode material layers is 400 μm.

[0118] This embodiment also provides a method for preparing the above-mentioned solid-state battery positive electrode, comprising the following steps:

[0119] S1: Preparation of composite cathode materials I

[0120] The positive electrode material and the solid electrolyte material were added to a planetary ball mill at a molar ratio of 100:10, and the first rough ball milling was performed at a rotation speed of 700 rpm for 7 hours, and then the second fine ball milling was performed at a rotation speed of 1100 rpm for 10 hours to obtain a composite positive electrode material I.

[0121] S2: Preparation of composite cathode materials II

[0122] The positive electrode material and the solid electrolyte material were added to a planetary ball mill at a molar ratio of 100:30, and the first rough ball milling was performed at a rotation speed of 800 rpm for 5 h, and then the second fine ball milling was performed at a rotation speed of 900 rpm for 12 h to obtain a composite positive electrode material II.

[0123] S3: Preparation of composite cathode materials III

[0124] The positive electrode material and the solid electrolyte material were added to a planetary ball mill at a molar ratio of 100:70, and the first rough ball milling was performed at a rotation speed of 650 rpm for 8 h, and then the second fine ball milling was performed at a rotation speed of 1000 rpm for 7 h to obtain a composite positive electrode material III.

[0125] S4: Preparation of composite cathode materials IV

[0126] The positive electrode material and the solid electrolyte material were added to a planetary ball mill at a molar ratio of 100:90, and the first rough ball milling was performed at a rotation speed of 750 rpm for 6 h, and then the second fine ball milling was performed at a rotation speed of 1050 rpm for 11 h to obtain a composite positive electrode material IV.

[0127] S5: Take the above-mentioned composite positive electrode material I, composite positive electrode material II, composite positive electrode material III and composite positive electrode material IV, and perform graded gradient assembly in the order of increasing molar content of solid electrolyte, and compact them at 250 MPa to obtain a gradient positive electrode product, that is, a solid-state battery positive electrode.

[0128] Application Example 5

[0129] This application example provides an all-solid-state battery, which differs from application example 1 in that the solid-state battery positive electrode of embodiment 1 is replaced by the solid-state battery positive electrode of embodiment 5.

[0130] Example 6

[0131] This embodiment provides a solid-state battery positive electrode, and its preparation method is different from that of Embodiment 1 in that the ball milling parameters of steps S1, S2 and S3 are all: a rotation speed of 500 rpm and a time of 12 h.

[0132] Application Example 6

[0133] This application example provides an all-solid-state battery, which differs from application example 1 in that the solid-state battery positive electrode of embodiment 1 is replaced by the solid-state battery positive electrode of embodiment 6.

[0134] Example 7

[0135] This embodiment provides a solid-state battery positive electrode, and its preparation method is different from that of Embodiment 1 in that the ball milling parameters of steps S1, S2 and S3 are all: a rotation speed of 800 rpm and a time of 12 h.

[0136] Application Example 7

[0137] This application example provides an all-solid-state battery, which differs from application example 1 in that the solid-state battery positive electrode of embodiment 1 is replaced by the solid-state battery positive electrode of embodiment 7.

[0138] Application Comparative Example 1

[0139] A solid-state battery is provided, which differs from Application Example 1 in that, in the positive electrode used, the positive electrode material and the solid electrolyte material are not distributed in a gradient manner, and the mass proportions of the positive electrode material and the solid electrolyte in each layer are the same.

[0140] Application Comparative Example 2

[0141] A solid-state battery is provided, which differs from Application Example 2 in that, in the positive electrode used, the positive electrode material and the solid electrolyte material are not distributed in a gradient manner, and the mass proportions of the positive electrode material and the solid electrolyte in each layer are the same.

[0142] Application Comparative Example 3

[0143] A solid-state battery is provided, which differs from Application Example 3 in that, in the positive electrode used, the positive electrode material and the solid electrolyte material are not distributed in a gradient manner, and the mass proportions of the positive electrode material and the solid electrolyte in each layer are the same.

[0144] The electrochemical performance test of the all-solid-state batteries of the corresponding examples 1-7 and the comparative examples 1-3 was carried out, and the test conditions were: the magnification of the application examples 1, 2, 4-7 and the comparative examples 1-3 was 0.1C, and the magnification of the application example 3 was 2C, and the initial discharge capacity and the capacity retention rate after a certain number of cycles were recorded. The test results are shown in Table 1.

[0145] Table 1

[0146]

[0147]

[0148] As can be seen from Table 1, the present invention can improve the discharge capacity and cycle performance of the solid-state battery by blending the positive electrode material and the solid electrolyte material and controlling the molar content of the solid electrolyte material to increase gradually in the thickness direction of the positive electrode.

[0149] At the same time, through the comparison of Application Example 1 and Application Comparative Examples 6-7, it can be seen that the positive electrode material exhibits excellent initial discharge capacity and higher capacity retention rate during the charge and discharge process by rough ball milling followed by fine ball milling compared with single ball milling. This can be attributed to the fact that the process of rough ball milling and fine ball milling enables the composite positive electrode to be fully crushed and mixed, weakening the barrier of lithium ions in the process of extraction and embedding, and exhibiting good charge and discharge performance.

[0150] By comparing Application Example 1 with Comparative Example 1, it can be seen that under the LCO@LPZSO│LPZSO│Li all-solid-state battery system, the full battery using the method of this patent exhibits excellent initial discharge capacity and a high capacity retention rate.

[0151] By comparing Application Example 2 with Comparative Example 2, it can be seen that under the S@LPMSI│LPMSI│Li-In all-solid-state battery system, the full battery using the method of this patent exhibits a higher capacity retention rate.

[0152] By comparing Application Example 3 with Application Comparative Example 3, it can be seen that under the LFP@NT-LLZO│NT-LLZO│Li-InF3 all-solid-state battery system, the full battery using the patented method exhibits excellent initial discharge capacity and a high capacity retention rate.

[0153] In summary, the positive electrode prepared by this patent improves the transition between traditional two-phase materials, accelerates the migration of lithium ions through multi-level diffusion mass transfer, optimizes the transmission characteristics of lithium ions between the positive electrode and the solid electrolyte interface, and stabilizes the insertion and extraction process of lithium ions, thereby effectively improving the electrochemical performance of the battery.

[0154] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A solid-state battery positive electrode, characterized in that: The solid-state battery positive electrode includes at least two positive electrode material layers, each of which includes a positive electrode material and a solid electrolyte material. The molar content of the solid electrolyte material in the positive electrode material layer increases from one side to the other side of the positive electrode.

2. The solid-state battery positive electrode according to claim 1, characterized in that: The number of the positive electrode material layers is 4 to 6.

3. The solid-state battery positive electrode according to claim 1 or 2, characterized in that: Between adjacent positive electrode material layers, the difference in molar content of the solid electrolyte material is 10% to 40% based on the molar amount of the positive electrode material.

4. The solid-state battery positive electrode according to any one of claims 1 to 3, characterized in that: In the positive electrode material layer, the molar content of the solid electrolyte material is 5% to 95% based on the molar amount of the positive electrode material; Preferably, the solid-state battery positive electrode includes 5 layers of positive electrode material layers, each of the positive electrode material layers includes positive electrode material and solid electrolyte material, and along the direction from one side of the positive electrode to the other side, the molar content of the solid electrolyte material in the positive electrode material layer is 5% to 15%, 25% to 35%, 45% to 55%, 65% to 75%, and 85% to 95%, respectively.

5. The solid-state battery positive electrode according to any one of claims 1 to 4, characterized in that: The total thickness of the positive electrode material layer is 10 μm to 500 μm.

6. The solid-state battery positive electrode according to any one of claims 1 to 5, characterized in that: The solid electrolyte material in each of the positive electrode material layers independently includes at least one of an oxide solid electrolyte and a sulfide solid electrolyte; Preferably, the oxide solid electrolyte comprises at least one of lithium zirconium phosphate oxide, lithium titanium phosphate oxide, lithium germanium phosphate oxide, lithium lanthanum titanium oxide, lithium lanthanum zirconium oxide and niobium-doped lithium lanthanum zirconium oxide; Preferably, the sulfide solid electrolyte includes at least one of lithium thiophosphate, argyrodite electrolyte, lithium germanium phosphosulfide, zinc-doped sulfide solid electrolyte and manganese-doped sulfide solid electrolyte.

7. A method for preparing a positive electrode of a solid-state battery according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: (1) mixing the cathode material and the solid electrolyte material by ball milling according to different mass ratios to obtain at least two series of composite cathode materials; (2) assembling the above-mentioned at least two series of composite positive electrode materials according to the increasing molar content of the solid electrolyte material, and compacting them to obtain the solid-state battery positive electrode; or, According to the increasing molar content of the solid electrolyte material, the above-mentioned at least two series of composite positive electrode materials are respectively prepared into slurries with a binder and a solvent and coated on the surface of the current collector. After drying, a solid-state battery positive electrode is obtained.

8. The preparation method according to claim 7, characterized in that: The ball milling mixing includes coarse ball milling and fine ball milling performed sequentially; Preferably, the process parameters of the rough ball milling are: rotation speed 400 rpm to 800 rpm, time 3 h to 8 h; Preferably, when the mass proportion of the sulfide solid electrolyte in the solid electrolyte material is ≥50%, the process parameters of the rough ball milling are: rotation speed 400 rpm to 600 rpm, time 3 h to 5 h; Preferably, when the mass proportion of the oxide solid electrolyte in the solid electrolyte material is ≥50%, the process parameters of the rough ball milling are: rotation speed 600 rpm to 800 rpm, time 5 h to 8 h; Preferably, the process parameters of the fine ball milling are: rotation speed 800rpm~1200rpm, time 6h~12h; Preferably, when the mass proportion of the sulfide solid electrolyte in the solid electrolyte material is ≥50%, the process parameters of the refined ball milling are: rotation speed 800 rpm to 1000 rpm, time 6 h to 8 h; Preferably, when the mass proportion of the oxide solid electrolyte in the solid electrolyte material is ≥50%, the process parameters of the fine ball milling are: rotation speed 1000rpm~1200rpm, time 8h~12h.

9. The preparation method according to claim 7 or 8, characterized in that: The compaction is carried out at a pressure of 100 MPa to 300 MPa; Preferably, when the mass proportion of the sulfide solid electrolyte in the solid electrolyte material is ≥50%, the compaction is performed at a pressure of 100 MPa to 150 MPa; Preferably, when the mass proportion of the oxide solid electrolyte in the solid electrolyte material is ≥50%, the compacting is performed under a pressure of 150 MPa to 300 MPa.

10. A solid-state battery, comprising a positive electrode, a negative electrode and a solid electrolyte layer located between the positive electrode and the negative electrode, characterized in that: The positive electrode adopts the solid-state battery positive electrode according to any one of claims 1 to 6, and the side with a high content of the solid electrolyte material in the solid-state battery positive electrode faces the solid electrolyte layer.